Comprehensive transformation of the health system of the Democratic Republic of Timor Leste (2013-2016) - Montero Díaz, Rolando; Santana López, Sandra; Carnota Lauzán, Orlando; Arocha Mariño, Carmen; Avalos García, María Isabel (Horizonte Sanitario, 2021)
Objective. Establish a comprehensive transformation of the health system of the Democratic Republic of Timor Leste (2013-2016). Materials and methods. A research / action type study was carried out from the managerial perspective, with an exhaustive use of methods, techniques and tools associated with the qualitative approach and health management in the Democratic Republic of Timor Leste, during the period 2013- 2016. Results. In a first phase, the situational analysis was carried out at the country level. With these elements, the strategic priorities, objectives, indicators and goals were successively defined for each perspective. Finally, the change program was organized, the transformation process was carried out and the results were determined. The National Cancer Program and the National Primary Care Program were designed and kept functioning; Missing medical specialties and care services were introduced; New approaches to human resource management were created and the level of scientific work was raised, among other benefits. Conclusions. There were substantial improvements in the health system and in addition, a potential capacity was created so that these effects continue to grow in quantity and quality. Keywords: health care reform, situational analysis, balanced scorecard, managerial technologies